Revitalization of Youth Roles in Preserving Customary Forests Through Citizen Journalism Training in Manurung Village, East Luwu Regency, South Sulawesi: Revitalisasi Peran Pemuda Mempertahankan Hutan Adat Melalui Pelatihan Jurnalisme Warga di Desa Manurung Kabupaten Luwu Timur Sulawesi Selatan - Idrus, Idham Irwansyah; Amsal, Bahrul; Mappe, Ulfa Utami; Sunaniah, Sunaniah; Ferdhiyadi, Ferdhiyadi (Institut Riset dan Publikasi Indonesia, 2026)
The community service program is carried out by providing ecological perspective Citizen Journalism training with the aim of (1) increasing knowledge about environmental awareness based on youth groups, (2) participants can implement well efforts to prevent environmental damage in maintaining customary forest areas, and (3) participants can disseminate knowledge about world views, traditions, and best practices regarding the protection of customary forest areas through journalistic writing. The main target audience for the community service activities are the Cerekang indigenous community, Customary Institutions, and Youth Groups in Manurung Village, East Luwu Regency, South Sulawesi. The results obtained in the community service program activities are increased knowledge and concepts of preventing ecological and customary-based environmental damage, increased understanding of the flow of prevention and reporting if they find environmental damage events, and participants in the Citizen Journalism training program can implement their understanding and attitudes into journalistic works in order to campaign for the importance of protecting the environmental ecosystem from all forms of natural damage. The outputs of PKM activities are (1) increased knowledge of participants regarding activity materials, (2) journalistic products in the form of essays and opinions in published newspapers, and (3) publication of PKM implementation in online media.